Wage moderation in the public sector: The experiences of 11 EMU countries in the recent economic crisis, 2008–2010. (November 2015) - Park, Sung Ho; Young, Kevin L
The factors that influence wage moderation policies across European countries have been a focus of industrial relations literature for some time. Given the lack of direct market discipline on public sector wages, most existing accounts suggest that the determinants of public sector wages are due to institutional characteristics of the national wage-setting system in question. In this article the authors suggest an alternative 'functionalist' explanation of public sector wage determination, with an emphasis on the role of public fiscal constraints and macroeconomic stress. Drawing on new data from 11 EMU countries during the recent economic crisis of 2008–2010 and engaging in a cross-national analysis using Fuzzy-Set Qualitative Comparative Analysis (fsQCA), the authors demonstrate that the functionalist explanation performs better than the institutionalist one in a crisis period.